Penetration Testing with Shellcode : Detect, exploit, and secure network-level and operating system vulnerabilities. - Megahed, Hamza (Packt Publishing, 2018)
Chapter 3: Assembly Language in Linux; Assembly language code structure; Data types; Hello world; Stack; Data manipulation; The mov instructionÂ ; Data swapping; Load effectiveÂ address; Arithmetic operations; Loops; Controlling the flow; Procedures; Logical operationsÂ ; Bitwise operations; Bit-shifting operations; Arithmetic shift operationÂ ; Logical shift; Rotate operation; SummaryÂ ; Chapter 4: Reverse Engineering; Debugging in Linux; Debugging in WindowsÂ ; Summary; Chapter 5: Creating Shellcode; The basics; Bad characters; The relative address techniqueÂ